1983
DOI: 10.1007/bf01871951
|View full text |Cite
|
Sign up to set email alerts
|

Influx mechanisms for Na+ and Cl− across the brush border membrane of leaky epithelia: A model and microelectrode study

Abstract: This paper presents a numerical model for the movement of Na+, K+, Cl-, H+ and HCO3- in a leaky epithelium. The model describes the active transport of Na+ and K+ at the serosal membrane and electrodiffusive permeation across the mucosal, serosal and junctional pathways. The model accounts for H+ and HCO3- production in the cell. The influx of Na+ and Cl- is assumed to occur mainly via Na/H and Cl/HCO3 exchange. The behavior of the cell, with this influx mechanism, is compared to a cell with an obligatory neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 52 publications
(54 reference statements)
3
11
0
Order By: Relevance
“…If the cotransport were actually a double exchange with indirect coupling of C1-and Na + influxes, the block of CI-entry should affect intracellular CI-activity rapidly, and Na + activity more slowly, as has been observed in Necturus gallbladder (Baerentsen, Giraldez & Zeuthen, 1983;Reuss, 1984). Moreover, the block of the cotransport by the appropriate reduction of luminal C1-concentration gives the same result obtained with SCN-treatment.…”
Section: The Na+-ci -Symport In the Absence Of Bicarbonatesupporting
confidence: 63%
“…If the cotransport were actually a double exchange with indirect coupling of C1-and Na + influxes, the block of CI-entry should affect intracellular CI-activity rapidly, and Na + activity more slowly, as has been observed in Necturus gallbladder (Baerentsen, Giraldez & Zeuthen, 1983;Reuss, 1984). Moreover, the block of the cotransport by the appropriate reduction of luminal C1-concentration gives the same result obtained with SCN-treatment.…”
Section: The Na+-ci -Symport In the Absence Of Bicarbonatesupporting
confidence: 63%
“…In other epithelia, Na+-CI -cotransport was found to be dependent on K + and to be due in fact to a Na+-K+-2C1 -symport (Frizzell & Field, 1984;Greger, 1984); similar findings were also reported for nonepithelial cells (Geck et al, 1980;Aiton et al, 1981;Ellory et al, 1982;Russell, 1983). Simple NaCI cotransport seems to exist in some epithelia (Fossat & Lahlou, 1979;Duffey & Frizzell, 1984;Frizzell & Field, 1984;Stokes, 1984;Alvo, Calamia & Eveloff, 1985) and in others is disputed (Baerentsen et al, 1983;Reuss, 1984;Spring, 1984).…”
Section: Introductionsupporting
confidence: 51%
“…The original model proposed for intestine (Nellans, Frizzell & Schultz, 1973) and gallbladder (Cremaschi, H6nin & Ferroni, 1974;Frizzell, Dugas & Schultz, 1975) was similar to that formulated by Crane for Na+-glucose cotransport (Crane, 1962). However, a Na+/H + and C1-/HCO~-double exchange was later revealed in many epithelia with a coupling between Na + and C1-due to cellular pH (Murer, Hopfer & Kinne, 1976;Liedtke & Hopfer, 1977;Petersen et al, 1981;Friedman & Andreoli, 1982;Liedtke & Hopfer, 1982a,b;Baerentsen, Giraldez & Zeuthen, 1983;Aronson & Seifter, 1984;Reuss, 1984). In other epithelia, Na+-CI -cotransport was found to be dependent on K + and to be due in fact to a Na+-K+-2C1 -symport (Frizzell & Field, 1984;Greger, 1984); similar findings were also reported for nonepithelial cells (Geck et al, 1980;Aiton et al, 1981;Ellory et al, 1982;Russell, 1983).…”
Section: Introductionmentioning
confidence: 94%
“…Steady-state measurements of ion activities cannot discriminate between cotransport and parallel Na+/H + and C1-/ HCO~ exchange (Reuss and Stoddard, 1987). Further, the proposed cotransport mechanisms are not consistent with the results of studies in which luminal solution pH, aCl,, pHi, and aNa~ + were measured during luminal solution ion replacements (Baerentsen et al, 1983;Reuss, 1984;Weinman and Reuss, 1984). On the basis of measurements of transient changes in intracellular ion activities, it was concluded that Na+/H + and C1 / HCO~ exchange could account quantitatively for salt entry across the apical membrane, estimating the latter from the rate of fluid absorption (Reuss, 1984).…”
Section: Introductionmentioning
confidence: 77%